Réseaux relationnels et éclectisme culturel - Armelle Bergé; Fabien Granjon (Revue LISA)
“Cultural omnivorousness” refers to the tendency to mix, in one’s cultural space, elements belonging to highbrow cultural forms with others which may be considered as popular or less legitimate. This article explores different patterns of cultural activities that mix differently ranked cultural elements, focusing on their relations to sociability. Drawing on examples from qualitative research, we show how cultural legitimacies can be produced by and worked out through the activities of groups and the ways in which cultural activities are combined and distributed, either in conversations — in talking — or in shared practices — in doing — according to the various groups that compose one’s relational network. Our hypothesis is that sociability and its different forms play an active role in the formation of omnivorous cultural tendencies and that, in return, the latter influence the differentiation of social frequentations. This article therefore concentrates on the architecture of relational practices and their peculiar forms when mobilising cultural contents that are heterogeneous in terms of their degree of legitimacy.